The Importance of Plant Emission Type on PM2.5 Impact Estimation: A Case Study of Nonpublic Anthracite Burning Facilities 사업장 배출형태에 따른 주변 지역 초미세먼지 농도 영향: 비민수용무연탄 배출원 사례 연구 - You, Seunghee; Kang, Yoon hee; Kim, Hyungcheon; Yoo, Chul; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2022)
Emission impacts of nonpublic anthracite burning facilities in Dangjin, Pohang, and Gwangyang before and after vertical reallocation of low-level emissions to elevated emissions on PM2.5 concentration were estimated with Community Multiscale Air Quality Modeling System (CMAQ) model simulations during the Korea-US Air Quality Study 2016. When CAPSS 2016, anthropogenic emissions inventory in South Korea, was examined, the low-level emissions explained more than 96% of the total primary PM2.5 and SO2 emissions, possibly due to uncontrolled emission factors applied during the emission estimate. Consequently, CMAQ simulations including the low-level emissions over-predicted PM2.5 and SO2 concentrations by up to 7.5 times and 9.2 times respectively of the observed concentrations at adjacent air quality monitoring stations. When the low-level emissions were vertically reallocated into elevated ones emitted from large stacks, their impacts on surface PM2.5 concentrations in surrounding areas decreased by up to 66-82%. In addition, the vertical reallocation lowered modeled PM2.5 concentrations by one-fifth, making them more comparable to the surface observations. The simulated SO2 concentrations at airborne measurement altitudes (300-500 m) increased only by a few ppb which is a fairly small change compared to the surface-level SO2 change after the vertical reallocation (i.e., a 28.5 ppb decrease of simulated SO2 concentrations in Gwangyang). It implies that not only the emission rates of air pollutants but also their precise release information should be prepared together prior to developing emission reduction plans and evaluating the effects on air pollution alleviation. Moreover, emission reduction plans should be evaluated in terms of ambient concentration rather than emission itself
Keywords: Low-level emissions; Pm2.5; Point source; So2; Vertical reallocation